Políticas nacionales, respuestas y desafíos para alcanzar el segundo objetivo de desarrollo del milenio: «Lograr la enseñanza primaria universal». Análisis comparativo entre Bangladesh y Perú - Manuel Pantoja; Saleh Ahmed (Pontificia Universidad Católica del Perú, 2011)
Country policies, responses and challenges to reach the United Nations Millennium Development Goals 2, 'Achieve Universal Primary Education'. Analysis comparison between Bangladesh and Peru Education is society's main instrument for reproducing itself and a compelling ingredient for lasting meaningful socioeconomic change. Therefore at the beginning of new millennium when the United Nations Member States was trying to reach a global consensus for global sustainability and development, issues related to universal primary education was a rational choice for them. This paper compares the status quoof this issue between Bangladesh and Peru, where 'development' takes place in reality. Mostly based on secondary research, this paper highlights the macro level comparative scenarios and challenges that how these two countries are putting their efforts and facing challenges in achieving universal primary education enrolment targets as part of their United Nations Millennium Development Goals commitments by 2015.